NARRATIVE OVERLAPPING IN SPATIAL TRAJECTORIES: EXPLORING THE PRODUCTION OF SPACE WITHIN THE EVERYDAY - Nurseto Nugroho; Yandi Andri Yatmo; Paramita Atmodiwirjo (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2019)
This paper discusses the production of space inside everyday using the narrative lens in architecture. The narrative in everyday is referred to as spatial trajectories. The study explores the spatial trajectories by analysing the story from a novel in order to identify the process of production of space within the everyday narrative. The inquiry results suggest that what is important in the production of space process is the bridge formed by the spatial trajectories. The more bridges that are present means, the more spatial trajectories are involved. It becomes important to consider the overlapping between spatial trajectories that occur in that space because it indicates various kinds of narratives involved.